The Effect of Environmental, Social, and Governance Disclosure on Firm Value - Devina Andreny Wongso; Tarsisius Renald Suganda; Daniel Sugama Stephanus (urn:nbn:id:umrah-jafi.v9i1.2025.001jiafi.v9i1, 2025)
This study examines the effect of ESG disclosure on firm value with a shareholder theory approach. This study uses a quantitative analysis of 147 observations of energy sector companies listed on the Indonesia Stock Exchange from 2021-2023. Firm value as the dependent variable is proxied by Tobin’s Q. The analysis shows that social, economic, and governance disclosures significantly adversely affect firm value. Meanwhile, ERM disclosures have a significant positive effect, while environmental disclosures do not affect firm value. These findings support the shareholder theory that assesses non-financial expenditure as a burden or waste of resources if they do not directly impact increasing profits. The study’s novelty lies in partially testing the five ESG aspects in the energy sector that are sensitive to greenwashing practices and market expectations. This research contributes to the development of ESG literature and provides insights for management and investors in emerging markets.